CHEKHOV'S MYTH IN RUNET FOLKLORE: BIOGRAPHICAL COMPONENT (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-20-33Chekhov’s surname, first name, patronymic and pseudonyms; appearance; profession (doctor and writer); trip to Sakhalin; pets; Josephine Pavlovna; Chekhov the playwright and his collaboration with Konstantin Stanislavsky are the subject of comic reinterpretation in Runet folklore. Although subject to demythologization, the image of A. P. Chekhov nevertheless emerges in the analyzed examples of Runet folklore (memes, jokes, anecdotes, rhymes) as an iconic figure, a paragon of intelligence. Key words: writer's myth, biographical component, Chekhov, online folklore, online poetry, mythologization, demythologization